The Effect of Mindfulness-Based Interventions on Tinnitus Distress. A Systematic Review - Rademaker, Maaike M.; Stegeman, Inge; Ho-Kang-You, Krysten E.; Stokroos, Robert J.; Smit, A. L. (Frontiers in Neurology, 2019)
Background: Tinnitus can be a disabling condition. Limited treatment options exist. Little is known about the effect of Mindfulness-Based Interventions (MBI) on tinnitus. Our objectives were to assess the effect of a Mindfulness-Based Intervention on 1) tinnitus burden and 2) depression and/or anxiety. Methods: a systematic search was conducted in PubMed Medline, EMBASE and PsycInfo combining the terms and synonyms of ‘’Tinnitus’’ and ‘’Mindfulness’’. The most recent search was performed on December 4th 2018. This systematic review was written according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). Two independent authors identified studies, assessed the risk of bias and extracted data. Studies were considered eligible if they included adults with tinnitus, performed a protocolled Mindfulness Based Intervention and measured tinnitus burden with a validated questionnaires. Studies were appraised with either the Cochrane Risk of Bias tool or the MINORS criteria, depending on their design. Results: The systematic search yielded seven articles. Three randomised controlled trials, three cohort studies and one comparative controlled trial. Two of three RCT’s showed a statistically significant decrease in tinnitus burden scores directly after treatment in the mindfulness group compared to the control group. One of three RCT’s showed a statistically significant effect of mindfulness therapy compared to the control group on a depression questionnaire directly post treatment. Conclusions: A decrease of tinnitus burden in Mindfulness Based Interventions can be observed directly post-therapy. No effect was observed for depression and anxiety in tinnitus patients. Long term effects remain uncertain. Mindfulness may have a place in tinnitus therapy, however the long term effects need to be researched.